Interdisciplinary results of an Italian research project on methane recovery and carbon dioxide storage in natural gas hydrate reservoirs - Beatrice Castellani; Rita Giovannetti; Umberta Tinivella; Salvatore F. Cannone; Roberto Fazioli; Fabio Trippetta; Michele Ciulla; Valentino Canale; Pietro Di Profio; Alberto Maria Gambelli; Andrea Nicolini; Giorgio Minelli; et al. (Green Carbon)
Natural gas hydrates (NGH) are found in marine sediments on continental and island slopes, deep-water sediments of inland lakes and seas, and polar sediments on continents and continental shelves. NGH constitutes the largest hydrocarbon resource on Earth, representing a reservoir of sustainable fuel owing to the possibility of a so-called CO2–CH4 replacement process. If CO2 is injected into NGH sediments, CH4 is released and CO2 hydrate formed. The extraction of gas from NGH, combined with carbon capture, presents significant potential advantages in the energy infrastructure and various economic and political contexts, aligning with future green policies. This study contributes to the advancement of knowledge by reviewing the findings of a three-year Italian research project focused on methane recovery and carbon dioxide disposal in NGH. The consortium comprises seven multidisciplinary Italian partners. This study introduces a novel process wherein the CO2–CH4 replacement process is integrated with methane purification and CO2 recirculation, which has been experimentally tested and represents a new advancement in gas hydrate science. Experimental tests at the microscopic and macroscopic levels showed that the efficiency of the process strongly depends on the mutual influence of the properties of water, sediment, and the involved gaseous species. Energy evaluations show that the ratio between the energy spent to complete an entire cycle of replacement and recirculation over the stored energy in the recovered methane is 17%, resulting in a beneficial energy balance, while economic analysis shows that the transition could generate—even in the short term—large high-impact cash-out.